2015
DOI: 10.1002/jcc.23978
|View full text |Cite
|
Sign up to set email alerts
|

H/D isotope effect on charge-inverted hydrogen-bonded systems: Systematic classification of three different types in H3XHYH3(X = C, Si, or Ge, and Y = B, Al, or Ga) with multicomponent calculation

Abstract: Three different H/D isotope effect in nine H3 XH(D)···YH3 (X = C, Si, or Ge, and Y = B, Al, or Ga) hydrogen-bonded (HB) systems are classified using MP2 level of multicomponent molecular orbital method, which can take account of the nuclear quantum nature of proton and deuteron. First, in the case of H3 CH(D)···YH3 (Y = B, Al, or Ge) HB systems, the deuterium (D) substitution induces the usual H/D geometrical isotope effect such as the contraction of covalent R(C-H(D)) bonds and the elongation of intermolecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…To improve the accuracy of MCMO calculations, we have to evaluate not only electron–electron correlation effect but also electron–nucleus and nucleus–nucleus correlation effects, since light nuclei are also treated quantum‐mechanically. We, however, considered only electron‐electron correlation effect in MCMO‐MP2 and MC‐DFT calculations in this study, because we already demonstrated that the H/D isotope effect on energies and geometries could be adequately evaluated without including electron–nucleus and nucleus‐nucleus correlation effects . We used the 6‐31G, 6‐31G*, 6‐31G**, 6‐31 + G**, 6‐31++G**, 6‐311G, 6‐311G**, and 6‐311++G** electronic basis sets to analyze the effect of the size of the electronic basis set on the distribution of nuclear wavefunction, and we adopt a single s ‐type GTF for the nuclear basis function.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To improve the accuracy of MCMO calculations, we have to evaluate not only electron–electron correlation effect but also electron–nucleus and nucleus–nucleus correlation effects, since light nuclei are also treated quantum‐mechanically. We, however, considered only electron‐electron correlation effect in MCMO‐MP2 and MC‐DFT calculations in this study, because we already demonstrated that the H/D isotope effect on energies and geometries could be adequately evaluated without including electron–nucleus and nucleus‐nucleus correlation effects . We used the 6‐31G, 6‐31G*, 6‐31G**, 6‐31 + G**, 6‐31++G**, 6‐311G, 6‐311G**, and 6‐311++G** electronic basis sets to analyze the effect of the size of the electronic basis set on the distribution of nuclear wavefunction, and we adopt a single s ‐type GTF for the nuclear basis function.…”
Section: Methodsmentioning
confidence: 99%
“…In the MCMO method, the concept of MOs for electrons is extended to the nuclear case and light nuclei are treated as quantum wavefunction as well as electrons under the fixed classical nuclei. The difference between nuclear quantum natures of isotopomers is directly reflected in the electronic states, and consequently our MCMO method can describe the H/D isotope effect on geometries (geometrical isotope effect: GIE) conveniently . Several groups also have developed their own multicomponent methods and successfully analyzed interesting chemical and physical phenomena .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the nuclear quantum nature of deuteron is less significant than proton, as mentioned above, the covalent X‐D length is shorter than the X‐H one. On the other hand, deuterium substitution leads the elongation of the hydrogen‐bonded H(D) … O distances, as seen in various hydrogen‐bonded systems . The TS structures are also relaxed by including NQE of proton and deuteron.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that there may be minor geometrical differences, for example, in the C2ÀH2 bond length, between ah ydrogenated and ad euterated version of 2 due to geometric isotope effects. [26] However,a sm entioned above, all CÀD bond lengths in 2 were fixed to tabulated CÀHv alues [11] already in the experimental multipole model of the ED distribution and, hence, also in the molecular single-point calculations. The electron localizability indicator [16] (ELI-D) was calculated and evaluated by using DGRID.…”
Section: Methodsmentioning
confidence: 99%